2020
DOI: 10.1590/1414-431x20209292
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1 is involved in type I IFNs-mediated systemic lupus erythematosus by up-regulating OAS2, OAS3, and OASL

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease associated with an aberrant activation of immune cells partly due to the dysfunction of cytokines such as type I interferons (IFNs). Long non-coding RNA MALAT1 has been found to play a pathogenic role in SLE; however, the underlying mechanisms are still poorly understood. Bioinformatics analysis showed the up-regulation of type I IFN downstream effectors OAS2, OAS3, and OASL (OAS-like) in CD4 + T cells, CD19 + B cells, and CD33 + myeloid cells in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…NONHSAT039491.2 was associated with lupus activity and the presence of anti-dsDNA, anti-RNP, and other neuropsychiatric manifestations. Gao et al [103] have found that MALTAT1 is involved in type 1 IFN-mediated SLE by up-regulating OAS2, OAS3, and OASL, confirming further the report by Ye et al [104] claiming that full high-throughput sequencing analysis of lncRNA expression profile in SLE-PBMCs could reveal a robust "IFN signature". A comprehensive review of ncRNA in SLE-CD4 + T cells with new insights into lupus pathogenesis has been published by Gao et al [105].…”
Section: Aberrant Intracellular Ncrna Expression Associated With Pathsupporting
confidence: 70%
“…NONHSAT039491.2 was associated with lupus activity and the presence of anti-dsDNA, anti-RNP, and other neuropsychiatric manifestations. Gao et al [103] have found that MALTAT1 is involved in type 1 IFN-mediated SLE by up-regulating OAS2, OAS3, and OASL, confirming further the report by Ye et al [104] claiming that full high-throughput sequencing analysis of lncRNA expression profile in SLE-PBMCs could reveal a robust "IFN signature". A comprehensive review of ncRNA in SLE-CD4 + T cells with new insights into lupus pathogenesis has been published by Gao et al [105].…”
Section: Aberrant Intracellular Ncrna Expression Associated With Pathsupporting
confidence: 70%
“…In light of this, OASL expression can be useful as a biomarker of SLE, as relative OASL mRNA expression levels are upregulated in active SLE patients and OASL may be a discriminant for systemic infection in SLE ( Ye et al, 2007 ). However, patients with active SLE who had renal disorders showed upregulated OASL in PBMCs and CD19 + B cells compared to that in patients without clinical manifestations ( Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This process results in cell death as a means to prevent viral survival and spread. While the association of OAS family members with autoimmunity is not new [ 27 , 28 , 29 , 30 , 31 ], the specific mechanisms by which OAS family members may contribute to autoimmunity is not well-described. In an individual with defects in clearing apoptotic cells, an anti-viral response via OAS family members could conceivably provide increased antigen or ligand for innate immune receptors such as Toll-like receptor 7 (TLR7) or other pattern recognition receptors.…”
Section: Discussionmentioning
confidence: 99%